Evaluating sustainability: a retrospective cohort analysis of the Oxfordshire therapeutic community. Issue 1 (December 2016) - Maughan, Daniel; Lillywhite, Rob; Pearce, Steve; Pillinger, Toby; Weich, Scott
Abstract Background Therapeutic communities (TCs) could reduce the health care use of people with personality disorder (Davies S, Campling P and Ryan K, Psychiatrist 23:79–83, 1999; Barr W, Kirkcaldy A, Horne A, Hodge S, Hellin K and Göpfert M, J Ment Health 19:412–421, 2010) and in turn reduce the financial and environmental costs of services. Our hypothesis is that 3 years following entry to a TC service, patients have reduced subsequent health care use and associated reductions in financial costs and carbon footprint. Methods A retrospective 4-year cohort study examined changes in health care use following entry to the Oxfordshire TC service. Comparative analysis was undertaken on a treated (n  = 40) and a control group (referred but who declined treatment;n  = 45). Financial costs and carbon footprint of health care use were calculated using national tariffs and standard carbon conversion factors. Mean changes in these outcomes were compared over 1, 2 and 3 years and adjusted for costs and carbon footprints in the year prior to joining the TC service. Results Compared to baseline, the group receiving TC care had greater reductions in financial costs and carbon footprint associated with A&E attendances (p  = 0.04) and crisis mental health appointments (p  = 0.04) than the control group. There were significantly greater reductions in carbon footprint for all secondary health care use, both physical and mental health care, after 3 years (p  = 0.04) in the TC group. Conclusions TC services may have the potential to reduce the financial cost and carbon footprint of health care.